Parenting interventions for mothers with problematic substance use: a systematic review of research and community practice - Milligan, Karen (Child maltreatment, 2020)
Women with problematic substance use are frequently referred to interventions to promote positive parenting. Parenting interventions that attend to the unique risks faced by this population may enhance engagement and outcomes. While reviews of extant parenting interventions in the research literature have been undertaken, no studies have examined parenting interventions being implemented in community practice and the extent to which these are informed by current research. We systematically compared parenting interventions offered in 12 maternal substance use treatment programs in one Canadian province with those described in the research literature (K = 21). Few parenting interventions were replicated, either within or across the two samples. However, parenting interventions within both samples were largely similar in their objectives. Across both research and community samples, approximately half of the interventions were developed or adapted for a problematic substance use population. Parenting knowledge, psychosocial risk, and maternal emotional regulation were most commonly addressed. Risks pertaining to the impact of drug craving and substance-related changes in neurobiology associted with parenting were less commonly addressed. Findings highlight current strengths and limitations of parenting interventions within research and community settings, with recommendations offered for future research and knowledge translation.